2015
DOI: 10.1177/0961203315610644
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and information searched for by French patients with systemic lupus erythematosus: A web-community data-driven online survey

Abstract: Online patient communities provide original unbiased information that can help improve provision of information to SLE patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…Seven of these studies (33.3%) identified a need for more interactive educational platforms with high-quality information, two (9.5%) demonstrated a need for the development of novel methods of disease monitoring, and two (9.5%) established a need for sources of support such as virtual communities. [24][25][26][27][28]30,32,34,35,39 Randomized Trials using mHealth technologies for SLE-The first randomized trial identified in the review compared the effects of cellular text messaging reminders with education on adherence to clinic visits (standard of care) in a cohort of 70 patients with childhood-onset SLE. Authors demonstrated that the use of text messaging reminders improved visit adherence, but not adherence to hydroxychloroquine.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Seven of these studies (33.3%) identified a need for more interactive educational platforms with high-quality information, two (9.5%) demonstrated a need for the development of novel methods of disease monitoring, and two (9.5%) established a need for sources of support such as virtual communities. [24][25][26][27][28]30,32,34,35,39 Randomized Trials using mHealth technologies for SLE-The first randomized trial identified in the review compared the effects of cellular text messaging reminders with education on adherence to clinic visits (standard of care) in a cohort of 70 patients with childhood-onset SLE. Authors demonstrated that the use of text messaging reminders improved visit adherence, but not adherence to hydroxychloroquine.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Of the included studies, 10 (48%) were observational, 4 (19%) were qualitative, 3 (14%) were reviews, 2 (9.5%) were randomized trials, and 2 (9.5%) were study protocols for future randomized trials. 10,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] The detailed characteristics of the included studies are described in Table 4. Among studies specifying a sample size, the median (range) number of SLE patients included was 84 (1-153).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a growing literature demonstrating that most patients, irrespective of demographics and underlying disease, prefer extensive disclosure of information related to treatments. 4,11 This is particularly important for physicians caring for patients with lupus and other chronic rheumatic diseases. In addition to efforts to provide more targeted therapies with fewer side-effects, efforts are needed to involve all patients in treatment decision-making as distinct preferences were documented in different patient groups.…”
Section: Discussionmentioning
confidence: 99%
“…Carenity is used by healthcare professionals as a vector to share online patient surveys. 4,5 The lupus community was created in France in 2011 and currently comprises 1568 patients.…”
Section: Introductionmentioning
confidence: 99%